Clinical Usefulness of 18F-FET PET in a Pediatric Patient With Suspected Demyelinating Disease. (5th August 2022) - Kang, Seo Young; Moon, Byung Seok; Yoo, Min Young; Yoon, Hai-Jeon; Kim, Bom Sahn
Abstract: An 11-year-old boy who presented with headache and progressive right-sided weakness exhibited cortical swelling in the parafalcine area of both frontoparietal high convexity and splenium portion of corpus callosum on brain MRI. This suggested the possibility of encephalopathy, but required differential diagnosis from brain tumor. 18 F-FET ( O -(2-[ 18 F]fluoroethyl)-l -tyrosine) PET/CT identified increased uptake along the parafalcine area of the frontoparietal lobes and the splenium portion of the corpus callosum. The relatively low target-to-background ratios were more indicative of inflammatory changes such as demyelinating disease. The patient recovered after empirical steroid and immunoglobulin treatment. Clinically, the patient was diagnosed with acute disseminated encephalomyelitis.